Hubungan Leadership Style Dan Self Efficacy Dengan Subjective Welll Being Pada Personil Satuan Lalu Lintas Kepolisian Resor Kota Deliserdang - Romi Syahputra; Rajab Lubis; Sjahril Effendy (Universitas Medan Area, 2022)
This study aims to determine the relationship between leadership style, self-efficacy and subjective well-being in the Traffic Unit Personnel of the Deliserdang City Police. The research method is a quantitative descriptive correlative type with a correlative study pattern by placing the research variables in two groups, namely the independent variable and the dependent variable. The research population is the Traffic Unit of the Deliserdang City Police, totaling 135 personnel. The sampling technique used is Proportional Random Sampling technique with the number of research subjects as many as 40 personnel, the data collection method uses a scale of leadership style and self-efficacy with subjective well being. Analysis of research data shows that (1) there is a significant positive relationship between leadership style and subjective well-being of employees/personnel of SAT LANTAS Polresta Deliserdang, as indicated by the coefficient rx1y = 0.687 and p 0.01; (2) there is a significant positive relationship between individual/personnel self-efficacy and subjective well-being in the Traffic Unit Personnel of the Deliserdang City Police, North Sumatra, as indicated by the coefficient rx2y = 0.108 and p 0.01; for the two hypotheses above, the product moment analysis technique is used; (3) there is a significant relationship between the leadership style of organizational leaders and individual/personnel self-efficacy with subjective well-being in the Traffic Unit Personnel of the Deliserdang City Police, North Sumatra, which is indicated by the coefficient F = 16,605; R = 0.688; R2 = 0.473 with p 0.01. Furthermore, the Standard error of estimate (SEE) is 16,33831. The accuracy rate is 100% - 16,33831 = 83.66169%. The third hypothesis in this study is to use Multiple Regression analysis.